1969
DOI: 10.2466/pr0.1969.25.3.911
|View full text |Cite
|
Sign up to set email alerts
|

Expectancies of Unemployable Males regarding Source of Control of Reinforcement

Abstract: Three groups of 60 22- to 28-yr.-old males, matched for age, socio-economic status and scholastic aptitude and classified as hard core unemployables were tested on the Rotter I-E Scale. No significant differences in alienation scores were noted between Group A whites and white college students. Group B Black Ss were significantly more externally controlled with greater variability of scores. Group C Mexican-Americans showed an even greater tendency in the external direction and greater variability than the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…These results reiterated the conclusions of other studies that family income and locus of control are related (Battle & Rotter, 1963;Scott & Phelan, 1969;Ramey & Campbell, 1976). Family income has also been shown to be related to overall achievement in academic areas (Madhere, 1977;Duncan & Brooks-Gunn, 2000;Grimes, et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…These results reiterated the conclusions of other studies that family income and locus of control are related (Battle & Rotter, 1963;Scott & Phelan, 1969;Ramey & Campbell, 1976). Family income has also been shown to be related to overall achievement in academic areas (Madhere, 1977;Duncan & Brooks-Gunn, 2000;Grimes, et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Scott and Phelan (1969) found that a group of chronically unemployed Mexican-American adults were more external than comparable White welfare recipients, but again no LOC differences were obtained among the adolescent children in the same community. This is particularly so when one of the entities is alien and may not structure the world in the same categories as the observer.…”
Section: Why Do Cross-cultural Research? Promises Promisesmentioning
confidence: 90%
“…Graves (1961) found that Anglo adolescents and adults feel greater personal control than their Chicano counterparts. Using a sample of subjects who had spent years on the welfare rolls and who were virtually unemployable, Scott and Phelan (1969) reported that Blacks and Mexican-Americans were less internal than Anglos. On the other hand, Jessor, Graves, Hanson, and Jessor (1968) were not able to replicate the the findings reported by Graves (1%1).…”
mentioning
confidence: 99%